Some methods of preponderance in resolving issues of modern biotechnology - Mohammad, Abdul Basir; Omar, Anwar Fakhri; Ahmad, Shofian; Mohd Nor, Amir Husin; Nasohah, Zaini; Mohd Kusrin, Zuliza; Ibrahim, Ibnor Azli; Muhammad Husni, Ahmad; Laluddin, Hayatullah; Samsudin, Muhammad Adib; El-Seoudi, Abdel Wadoud Moustafa Moursi; Samuri, Mohd Al-Adib; et al. (Medwell Publications, 2012)
The development of modern biotechnological plants through genetic engineering techniques is a method to improve the quality of crops in terms of quality and quantity. However, the debate among scientists and Muslim scholars in regarding with public interest and public corruption as to plant products that produced by modern biotechnology which is well-known now a days as Genetically Modified (GM) food is never stop. Thus, in the Islamic law there are a few methods of preponderance or predominance which could be used in order to find out the best way out of confusion in certain cases for legal rulings, especially in the cases relating to GM food. The objectives of this study are to examine the considerations of maslahah and mafsadah in purposes of Islamic law in relating to issues of modern biotechnology and to elucidate the methods of preponderance as well. It is important to understand here is everything that existed on this earth whether it occurs naturally or is present through the efforts of research and human expertise, all have benefits or advantages and risks or disadvantages. In the view of Islamic law if a biotechnological product is produced by hybrid efforts of using unlawful genes it is certainly clear can be categorized as illegal to be consumed then it becomes forbidden. But however, there are many products that are produced through biotechnological processes are unclearly able to decide easily whether they are lawful or unlawful for consumption by consumers. As such, a few methods laid down in this study are the first attempt to give a way out of difficulties for easily making legal rulings in this issue. So, it is hoped that the substance of this study will give an initial guidance for Muslim scholars to make legal judgment if they are facing the issues of GM food